Prospects for the development of technology air conditioning - Chernyshova, O. V.; Khrystyan, Ye. V.; Tytarenko, I. V. (Science and Transport Progress, 2008)
In the article the evaporation cooling and spray (aqueous and air-to-water) types of the air-conditioning systems are considered, their merits and demerits are analyzed; the new scheme of a conditioner is offered.